Prophet Muhammad : The Night Journey - Khan,Saniyasnain (Goodword books, 2024)
A beautifully illustrated board book that introduces toddlers and preschoolers to the miraculous Night Journey (Al-Isra wal-Mi$1 (Braj) of Prophet Muhammad (PBUH). Using simple, age-appropriate language and captivating illustrations, it highlights the Prophet$1 (Bs journey, the importance of prayer, Allah$1 (Bs mercy, and the Prophet$1 (Bs special status in Islam.s
An engaging board book retelling of the Prophet Muhammad$1 (Bs (PBUH) Night Journey (Al-Isra wal-Mi$1 (Braj) for young children. Presented in clear, age-appropriate language with colorful illustrations, the book emphasizes key Islamic lessons including the significance of prayer, faith in Allah$1 (Bs mercy, and the honored role of the Prophet. The sturdy board book design makes it ideal for repeated reading and family sharing.s
Best suited for children under 5 years of age $1 (Btoddlers and preschoolers.s